2005
DOI: 10.1021/jo0507688
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluorine on the Structures and Energetics of the Propynyl and Propargyl Radicals and Their Anions

Abstract: [reaction: see text] The adiabatic electron affinity (EA(ad)) of the CH(3)-C[triple bond]C(*) radical [experiment = 2.718 +/- 0.008 eV] and the gas-phase basicity of the CH(3)-C[triple bond]C:(-) anion [experiment = 373.4 +/- 2 kcal/mol] have been compared with those of their fluorine derivatives. The latter are studied using theoretical methods. It is found that there are large effects on the electron affinities and gas-phase basicities as the H atoms of the alpha-CH(3) group in the propynyl system are substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…21͒ eV. The presence of such a low-lying degenerate excited state can cause artificial symmetry breaking of the wave function in single reference calculations and lead to distortion from the C 3v geometry, 20,26 as has been seen in calculations on the NO 3 radical. 27 Moreover, possible combinations of Jahn-Teller and pseudo-Jahn-Teller effects can lead to a very complicated vibronic spectrum.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…21͒ eV. The presence of such a low-lying degenerate excited state can cause artificial symmetry breaking of the wave function in single reference calculations and lead to distortion from the C 3v geometry, 20,26 as has been seen in calculations on the NO 3 radical. 27 Moreover, possible combinations of Jahn-Teller and pseudo-Jahn-Teller effects can lead to a very complicated vibronic spectrum.…”
Section: Introductionmentioning
confidence: 94%
“…This doublet was attributed to a split of the degeneracy of the 2 E ground state in which the unpaired electron is in the orbital of the triple bond, based on the early theoretical work by Bauschlicher and Langhoff. 25 However, subsequent calculations 1,[18][19][20][21][22]26 converged to a 2 A 1 or 2 AЈ ground state with the unpaired electron in a nonbonding sp orbital on the terminal carbon. The "" state has been calculated to be an extremely low-lying excited state with vertical excitation energy between 0.04 ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…This work reports the gas‐phase basicity of propynyl anions as the difference in the sum of electronic and thermal free energies of the anion and the neutral molecules, as well as the thermal correction to the Gibbs free energy 16…”
Section: Computational Detailsmentioning
confidence: 99%
“…Zhang15 has reported the results of a study of the acidity of the acetylenic proton and the CH bond dissociation enthalpies in fluorine derivatives of propyne and also in the neutrals and radicals of various substrates by ab initio calculations. Sreeruttun et al have observed the effects of fluorine on the structures and energetics of propynyl radicals and their anions 16…”
Section: Introductionmentioning
confidence: 99%
“…The methylethynyl (also called propynyl) radical (•CCCH 3 ) is a significant chemical in hydrocarbon chemistry 8. Sreeruttun et al 9. have studied the effects of fluorine on the structures and energetics of the derivatives of propynyl (•CCCH 3 ) and propargyl (CHCCH 2 •) radicals and their anions ( − :CCCH 3 and CHCCH 2 : − ).…”
Section: Introductionmentioning
confidence: 99%